Characterization of spatial variability with observed responses: application of displacement back estimation - Sun, Yi-xuan; Zhang, Lu-lu; Yang, Hao-qing; Zhang, Jie; Cao, Zi-jun; Cui, Qi; Yan, Jun-yi (Journal of Zhejiang University. A. Science, 2020)
Soil spatial variability is difficult to evaluate due to insufficient test data. An alternative option is estimation by indirect methods such as inverse analysis. In this paper, two examples are presented to demonstrate the capability and accuracy of the probabilistic estimation method to characterize soil spatial variability with displacement responses. The first example is a soil slope subject to a surcharge load, in which the spatially varied field of the elastic modulus is estimated with displacements. The results show that estimations based on horizontal displacements were more accurate than those based on vertical displacements. The accuracy of the estimated field was substantially reduced by increasing variance of elastic modulus. However, the estimation was generally acceptable as the error was not more than 10%, even for the high variance case (COV E =1.5). The accuracy of estimation was also affected by the type of covariance function and the correlation length. When the correlation length decreased, the accuracy of estimation was reduced. The second example is a validation of laboratory model tests where a horizontal load was applied on a layered ground. The estimated thicknesses of soil layers were close to those in the real situation, which demonstrates the capacity of the estimation method.